2015
DOI: 10.1155/2015/651369
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Macrophytic Typology of Belgian Reference Watercourses

Abstract: The objective of the study is to create a typology of macrophytes for the reference watercourses of the Meuse River catchment basin in Wallonia as a step towards the implementation of the European Water Framework Directive. The 50 sites studied are the object of a physicochemical and environmental characterization followed by a floristic survey (phanerogams, mosses, liverworts, and macroalgae). Six clusters of watercourses with their characteristic species are highlighted by two-way clustering and indicator sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…These studies may address a wider range of conditions than in the present study and suggest that this relationship is scaledependent. The majority of the richest sites were characterized by PO 4 concentration < 0.1 mg⋅L −1 which is very close to the 0.05 mg⋅L −1 threshold determined by Galoux et al [41] for the reference conditions of Walloon watercourses. Brusa and Cerabolini [11] in Italy using multivariate analysis found that the 3 major factors explaining their species assemblages were the permanency/nonpermanency of the water flow, the slope, and the canopy cover.…”
Section: Species Richnesssupporting
confidence: 82%
See 3 more Smart Citations
“…These studies may address a wider range of conditions than in the present study and suggest that this relationship is scaledependent. The majority of the richest sites were characterized by PO 4 concentration < 0.1 mg⋅L −1 which is very close to the 0.05 mg⋅L −1 threshold determined by Galoux et al [41] for the reference conditions of Walloon watercourses. Brusa and Cerabolini [11] in Italy using multivariate analysis found that the 3 major factors explaining their species assemblages were the permanency/nonpermanency of the water flow, the slope, and the canopy cover.…”
Section: Species Richnesssupporting
confidence: 82%
“…This suggests that other variables not measured here could explain better the observed species assemblages. Following other authors [41,42], we suggest that factors such as the substrate itself (sand, loam, and rock), the micro topography [11,16,18,33,43], the water turbulence [2,8,44], the distance from the spring [8,13], the presence and characteristics of travertine-productive microorganisms like cyanobacteria [8,16,45], and the local relative humidity could…”
Section: Global Analysissupporting
confidence: 62%
See 2 more Smart Citations
“…Between 2007 and 2013, this network undertook several macrophytic surveys of waterbodies [27]. The reference macrophytic communities were waterbodies classified by the Walloon Government as being areas showing little or no human impact [28].…”
Section: Introductionmentioning
confidence: 99%